Profits and Politics: Coordinating Technology Adoption in Agriculture - Rohini Pande (Yale University, Economic Growth Center, 2005)
This paper examines the political economy of coordination in a simple two-sector model in which individuals' choice of agricultural technology affects industrialization. We demonstrate the existence of multiple equilibria; the economy is either characterized by the use of a traditional agricultural technology and a low level of industrialization or the use of a mechanized technology and a high level of industrialization. Relative to the traditional technology, the mechanized technology increases output but leaves some population groups worse off. We show that the distributional implications of choosing the mechanized technology restrict the possibility of Pareto-improving coordination by an elected policy-maker, even when we allow for income redistribution.
Keywords: O14; H10; 330; Industrialization; Choice of Technology; Government Policy; Industrialisierung; Technologiewahl; Agrartechnik; Neue politische Ökonomie; Theorie